Development of a dynamic standard of pressure - Díaz Tey, Alberto (2017)
Based on the fact that there is no reported measurement and calibration capacity for dynamic pressure measurements, a reference standard is statistically characterized from the pressure of the first reflection of the shock wave produced by the expansion of a gas in a shock tube. The direct comparison of the pressure measurements in the stabilization time allows to evaluate the behavior of a pressure transducer by the effect of the validated aperiodic perturbation and thus, to infer its metrological performance in the indirect measurement of the height of the marine waves at depths of up to 25 m, very important in the design of maritime structures. The performance of reference standard was validated for air and 2 m length of the driven section. The results are reported in terms of reproducibility of the pressure in the laboratory by the standard uncertainty pooled, with relative uncertainty of 2,72% for disturbed air pressures equal to 137,01 hPa.